2018
DOI: 10.1504/ijev.2018.10008386
|View full text |Cite
|
Sign up to set email alerts
|

Think Big or Small is Beautiful. An empirical analysis of characteristics and determinants of success of sustainable crowdfunding projects

Abstract: This paper deals with crowdfunding for sustainable ventures. It uses an empirical dataset gained from the two largest sustainability-oriented crowdfunding platforms in Germany. In a first step, common characteristics of sustainable crowdfunding projects are identified and categorised based on an established framework for classifying sustainable entrepreneurship. In a second step, linear and logistic regression models are used to analyse the drivers of financial and marketing success of sustainable crowdfunding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…They found that technology risk decreases the excess of return of projects. Hörisch [36] analyzed factors influencing sustainable projects to succeed in financing and marketing using linear and logistic regression models. Updates made during campaigns are among the identified features with positive influence for sustainable projects to meet their funding targets.…”
Section: Related Workmentioning
confidence: 99%
“…They found that technology risk decreases the excess of return of projects. Hörisch [36] analyzed factors influencing sustainable projects to succeed in financing and marketing using linear and logistic regression models. Updates made during campaigns are among the identified features with positive influence for sustainable projects to meet their funding targets.…”
Section: Related Workmentioning
confidence: 99%
“…Concerning theoretical contributions, literature already recognizes the importance of project‐related (Calic & Mosakowski, ; Hörisch, ; Hörisch, ), founder‐related (Bonzanini et al, ; Calic & Mosakowski, ), project finance‐related (Bonzanini et al, ), and platform‐related (Bonzanini et al, ; Calic & Mosakowski, ; Vasileiadou et al, ) attributes on SO campaigns' success. To our knowledge, there are no studies that have instead addressed the role of specific product/service attributes pursued within SO campaigns in determining the success of such campaigns and thus the extent to which CF can support funding of SO projects.…”
Section: Conclusion Limitations and Future Developmentsmentioning
confidence: 99%
“…However, funding is a critical phase in new business formation (Shane 2003), especially in the case of sustainable entrepreneurs as their non-traditional business view might lead to difficulties in attracting traditional investors (Choi and Gray, 2008). According to previous studies (Hörisch, 2015(Hörisch, , 2018Ortas et al, 2013), they often experience a lack of funding. The need to balance economic, social and environmental goals makes sustainable businesses more ambiguous and therefore less attractive for traditional investors compared to purely profit-oriented firms (Messeni Petruzzelli et al, 2019).…”
Section: Theoretical Background 21 Sustainable Entrepreneurship: Pementioning
confidence: 99%
“…Despite the increasing importance of sustainable crowdfunding, research on this topic remains limited (Messeni Petruzzelli et al, 2019;Testa et al, 2019). There are rather contradictory findings around the success of sustainable crowdfunding campaigns (Hörisch, 2015(Hörisch, , 2018Calic and Mosakowski, 2016;Vismara, 2019), and there is a need to adapt findings from the general crowdfunding literature to the context of sustainable crowdfunding. Researchers have begun to explore the peculiarities of sustainable crowdfunding (e.g.…”
Section: Contribution and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation